Global food security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Global food security: the need to stimulate food demand and increase food production by Joachim von Braun, Special Paper CTA Annual Report 1991 available from CTA